Biomimicry architecture: new dimensions of creativity an exploratory approach in academia - F. M. Mohamed, Mohamed; ., . (International Journal of Engineering and Technology, 2018)
The Universe around us stands as a proof of the greatness of God. Everything around us, small or huge, tiny or great, all confirms the fact that this universe has a creator who initiated it and kept running and maintaining it. No one can ignore such fact. Allah has created all aspects of beauty and perfection. Despite the vast technological and scientific development that humanity witness these days, yet we still discover new indications of God's creativity and miraculous formations every day. This fact was the source of inspiration for architectur- al designers in coming up with new inventions and creations that help regeneration and natural environmental sustainability. â€œBiomimic- ryâ€ is certainly one of these approaches that consider nature as its inspiration towards a different â€“hopefully, a better - future for humani- ty. This research sheds some light on a vision that took place in fall2014 at the department of architecture, Effat University, KSA. A senior studio (studio7) was targeted to explore the potential of weaving the â€œBiomimicryâ€ approach within the syllabus of that studio. This initiative had been proposed by the team supervising this studio as an exploratory one before the call from â€œMakkah Techno-valley Company (MTV)â€ to design a Research Center (RIM) was launched. The RIM project aspires to play a major role in offering a support- ive environment for youth in Saudi Arabia enhancing their abilities and developing their skills to experience achievement within â€œMTVâ€ main campus. The study aimed at exploring the possibilities of implementing such an approach within a GCC country with its entire unique educational context.Â Â